Impact of Performance Evaluation on Employees’ Productivity in Deposit Money Banks in Lagos State, Nigeria - Odunayo, H A (European Journal of Human Resource, 2022)
Purpose: Performance evaluation is an element of performance management which is planned to increase productivity and provides an opportunity to continuously review business objectives. Some researchers have indicated that many managers felt that performance evaluation did not add value or help achieve business objectives while many workers found it a bother. In Nigeria, performance evaluation has been embraced by both the public and private sectors as a tool for performance improvement. The assessment of its effectiveness, however, has been hampered. This study sought to determine the effect of performance evaluation on employee productivity in deposit money banks in Lagos State. Methodology: The study adopts survey research design. The population of this study consist of 192 employees of two selected Deposit Money Banks in Lagos State. The study adopted total enumeration method in determining the sample size. The study collected primary data with the help of questionnaire. Data was collected from respondents using a structured questionnaire. Ordinary least square regression model was used to assess the nature and degree of relationship between dependent variable and independent variables. Findings: Findings from the study indicated that the use of performance appraisal has significant effect on employee productivity. Specifically, findings revealed that managerial review and peer review have significant effect and enhanced employee productivity. Recommendation: The study recommends that management should adopt successful management styles which involve building teams, networks of relationships, and developing and motivating others which would instil skills to the employees and which have a critical role in improving the level of productivity of the employees.